THE STRUCTURAL MODEL OF ECONOMIC HARDSHIP AND SUBJECTIVE WELL-BEING AMONG VULNERABLE PEOPLE - Ismail, Noraini; Hj. Paim, Laily; Abu Samah, Asnarulkhadi; Awang, Mohd Daud (Journal of Techno-Social, 2015)
The present study aims to illustrate the relationship between economic hardship and the subjective well-being (SWB) of household heads in Malaysia who are vulnerable to poverty.Economic shortcomings challenge the well-being (WB) of Malaysian families and has the most inclination to effect vulnerable impoverished groups in the lower parts of the income distribution. SWB is the ultimate goal of public policy and individuals. Varying experiences of SWB were reported by people. SWB is connected with aspects which people value in their lives. Some individuals experience high levels of SWB despite adverse living conditions, while others experience low levels of SWB despite having certain outward advantages. The empirical literature on the association between economic hardship and SWB indicates that they are only moderately correlated to one another.This study utilised data collected in 2010 using instruments of â€œVulnerability Development Indexâ€, designed for the research of Vulnerability Index by a group of researchers in the Faculty of Human Ecology, Universiti Putra Malaysia. The study survey sample was made up of 379 participants of vulnerable household heads in Selangor.The study discovered that the economic hardship had a significant negative relationship with SWB. Within samples of the study, household headsâ€™ level of economic hardship was found to be relatively low, and had a reasonably strong negative association with SWB. Test of Measurement Model and Structural Model produced with acceptable fit statistics. It was estimated that the economic hardship explained only 10 percent of SWB. The result indicated that having lower economic hardship was associated with higher level of SWB.Based on the principal of the Theorem of Incomparable Utilities, this study proved that despite many economic hardships encountered by the individual, he or she still acknowledged life as very good/very happy. SWB builds on hardship because people tend to be happier after enduring hard times.